Novel magnetic hollow zein nanoparticles for preconcentration of chlorpyrifos from water and soil samples prior to analysis via high-performance liquid chromatography (HPLC). Issue 9 (18th April 2018) - Rahimi Moghadam, Mojtaba; Zargar, Behrooz; Rastegarzadeh, Saadat
Abstract : Herein, magnetically hollow zein nanoparticles were synthesized and used as a magnetic sorbent for the preconcentration of chlorpyrifos and its analysis by high-performance liquid chromatography (HPLC). Abstract : Herein, magnetically hollow zein nanoparticles were synthesized and used as a magnetic sorbent for the preconcentration of chlorpyrifos and its analysis by high-performance liquid chromatography (HPLC). Morphology of the sorbent was characterized by transmission electron microscopy (TEM). In this study, the effects of important parameters such as pH of the solution, adsorption and desorption time, type and volume of desorption solvent, and salt addition were investigated. Under optimized experimental conditions, the linear range was from 50 to 2000 μg mL −1, and an LOD of 25 μg L −1 was calculated. The relative standard deviations (RSD) varied from 3.8 to 5.1% ( n = 5). The enrichment factors for 50 and 100 μg L −1 samples were calculated as 187 and 210, respectively. The developed method was successfully applied in soil and water samples and showed good extraction recoveries.